Revision of the genus Phoxoserphus Lin, 1988 (Hymenoptera: Proctotrupidae), with the description of a new species - Abe, Junta (Zootaxa, 2023)
The genus Phoxoserphus Lin, 1988 is revised. The morphological variations not previously mentioned in the known species, Ph. chikoi and Ph. vescus, are briefly discussed, and Ph. iyokpe sp. nov. is described as new to science. Additionally, new morphological characters useful for species identification are proposed. An updated diagnosis and key to species are provided.